Students' Analytical Thinking Skills in Social Science Subjects in Elementary Schools: CORE Learning Model - Astuti, Lia Nurma Widi; Sodiq, Ahmad; Yanti, Yuli (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study sought to evaluate the influence of the CORE learning model on the analytical thinking skills of fourth-grade elementary students. This study utilized Class IV A as both the experimental and control group. A cohort of 42 fourth-grade students from SDS Swadhipa Natar participated in this study. The control group employed a problem-based learning approach, whereas the experimental group utilized a learning CORE model. This study utilized a quantitative methodology using a quasi-experimental design. This study employed purposive sampling to choose individuals, designating class IV A (experimental group) and class IV B (control group). This study's findings demonstrate that the CORE learning technique enhances students' analytical thinking abilities in Chapter 8 of the IPAS Lesson, which emphasizes the cultivation of a civilized society. Class IV A, implementing the CORE learning model, achieved an average score of 87.82, whilst Class IV B, utilizing the problem-based learning model, attained an average score of 78.77. The conclusion is corroborated by t-test results indicating a significance level of 0.000. Given that the significance level of 0.000 is below 0.05, we may conclude that the application of the CORE learning model significantly influences students' analytical thinking skills.